ACADEMIC WRITING COMPETENCY BY USING BLENDED LEARNING STRATEGY - Sartika Dewi Harahap; Syamsiah Depalina Siregar (Journal of English Education and Linguistics, 2022)
Covid 19 disease has brought the new atmosphere for teaching and learning process. Where the real activity for lectures and students was very limited to do face-to-face activity. It is the fact that education and other side of world activity forced now. Learning from Home (LFH) as the one of alternative instructed by stakeholder to carry out the teaching and learning even though they are not in the classroom. This study present how the blended learning will be applied in academic writing Subject. This study is a case study design where the writer describes and evaluates blended learning in Academic Writing subject learning process to deliver the materials based on syllabus, writing practice by doing task, assignment submission and grading, students concern with the teachers’ elaboration and Foreign Language action and students evaluation. The participants will allow in this study are 13 students of ffifth semester students of English Education Program, Mandailing Natal Islamic State Collage. The data is collected through observation and short interview analysis. The result of this study shows that the students appreciated and benefited from the blended learning used in Academic Writing Subject. It help motivated the students to became independent learners and increase their ability in writing paragraph, essay, undergraduate proposal or thesis and so on.